Provider activity and social rights - Delpiazzo, Carlos E. (2020)
The article focuses in the social dimension of administrative serviciality in Constitutional Rule of Law State, emphasizing in the look from social rights.The empowerment of social dimension of performance of administrative function and requirements of management of general welfare are requirements imposed by the centrality in human person.